'Looping effects' related to young people's mental health: How young people transform the meaning of psychiatric concepts. Issue 1 (March 2020) - Lindholm, Sofia Kvist; Wickström, Anette
Over the past decades, reports from official authorities and the media have suggested that there is a 'crisis' in young people's mental health. However, there is considerable uncertainty regarding how to interpret the data referred to in these alarming reports. The present article draws on 'the minority voices' of young people and theories developed by Ian Hacking to undertake a critical analysis of the conceptualisation of young people's mental health. According to Hacking, systems of classifications formulate general truths about people and frame the suffering of individuals in specific ways. Classification changes people. However, young people are social actors who interact with classifications of their mental health and by doing so they could cause classifications to be redrawn. Hacking refers to these feedback effects as 'looping effects'. Based on 51 interviews with 15-year-olds, this article explores how young people interact with psychiatric labels associated with their wellbeing such as anxiety and depression . We demonstrate how the participants gave new meaning to these psychiatric labels, devalued and gave nuance to them, and by doing so transformed them into cultural categories rather than diagnostic categories . We discuss the potential looping effects related to young people's mental health and how the present findings can inform policy practice.